2022
DOI: 10.1002/aenm.202201783
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Decorated Iron Carbide Nanoparticles Heated by Magnetic Induction as Adaptive Multifunctional Catalysts for the Selective Hydrodeoxygenation of Aldehydes

Abstract: an important transformation for the fine chemical and pharmaceutical industries, and is also considered an important enabler for chemical energy conversion and especially for the upgrading of biomass feedstock to value-added chemicals. [1] In particular, the selective hydrodeoxygenation of renewable platform chemicals such as furfural, hydroxymethylfurfural and vanillin has attracted tremendous attention in the past years. [2] This requires selectively hydrodeoxygenating aromatic aldehydes, while leaving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…Supported Pd nanomaterials have been shown as one of the most powerful catalysts for the selective hydrogenation reaction. , In addition, the use of magnetic induction heating of magnetic nanomaterials in catalytic reactions has recently emerged as a hot field. This localized heating technology is significant in facilitating organic transformations under mild conditions. Hence, we investigated the Pd-loaded split core–shell catalyst (M2) for the selective hydrogenation of crotonaldehyde to butanal under the induction of an alternative magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…Supported Pd nanomaterials have been shown as one of the most powerful catalysts for the selective hydrogenation reaction. , In addition, the use of magnetic induction heating of magnetic nanomaterials in catalytic reactions has recently emerged as a hot field. This localized heating technology is significant in facilitating organic transformations under mild conditions. Hence, we investigated the Pd-loaded split core–shell catalyst (M2) for the selective hydrogenation of crotonaldehyde to butanal under the induction of an alternative magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…Such immediate response from the catalyst to the magnetic field is of great interest to tackle the industrial challenges associated with intermittent electricity supply. Subsequently, it was demonstrated that inversely catalytically active metal particles can be deposited also on ICNPs or other suitable magnetic NPs potentially allowing for even more direct heat dissipation (e.g., Ni@ICNPs, [9b] Ru@ICNPs, [11] Cu@ICNPs, [12] Ni@FeNi 3 [13] ). Demonstrating the potential for adaptive catalysis, multifunctional Cu@ICNPs systems proved highly active for hydrodeoxygenation [12] reactions under magnetically induced heating, showing again an immediate response to the magnetic field induced by intermittent electricity supply.…”
Section: Temperaturementioning
confidence: 99%
“…In order to quantify the heating power, the specific absorption rate (SAR) was introduced to describe the amount of energy absorbed per unit of mass and was expressed in watts per gram (W g −1 ). [9,11] The hollow yolkshell nanoreactors displayed a high SAR value of ≈150 W g −1 at a m 0 H rms of 60 mT with a fixed frequency of 100 kHz (Figure S10, Supporting Information), which was mainly attributed to the good dispersibility in solution (Figure S11, Supporting Information) and the adequate saturation magnetization (Figure S12, Supporting Information) characterized by vibrating sample magnetometer.…”
Section: Fabricating and Structural Characterizationmentioning
confidence: 99%